2015
DOI: 10.1002/chem.201501122
|View full text |Cite
|
Sign up to set email alerts
|

[Cu32(H)20{S2P(OiPr)2}12]: The Largest Number of Hydrides Recorded in a Molecular Nanocluster by Neutron Diffraction

Abstract: An air- and moisture-stable nanoscale polyhydrido copper cluster [Cu32 (H)20 {S2 P(OiPr)2 }12 ] (1H ) was synthesized and structurally characterized. The molecular structure of 1H exhibits a hexacapped pseudo-rhombohedral core of 14 Cu atoms sandwiched between two nestlike triangular cupola fragments of (2×9) Cu atoms in an elongated triangular gyrobicupola polyhedron. The discrete Cu32 cluster is stabilized by 12 dithiophosphate ligands and a record number of 20 hydride ligands, which were found by high-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(144 citation statements)
references
References 66 publications
5
139
0
Order By: Relevance
“…The structure of 2 (R= i Pr) can be derived from that of 1 by simply removing one of the capping atoms lying on the C 3 axis, with only minor additional changes in the overall connectivity and shape of the molecule. This is reminiscent of the structural and chemical relationships between [M 8 (H){E 2 P(OR) 2 } 6 ] + and [M 7 (H){E 2 P(OR) 2 } 6 ] (M=Cu, Ag; E=S, Se) . The structure of cluster 3 (R= n Pr) can be derived from that of 2 by simply shifting off the capping atom lying on the C 3 axis, generating a chiral structure of C 1 symmetry and revealing structural isomerism in the Ag 20 core.…”
Section: Figurementioning
confidence: 96%
“…The structure of 2 (R= i Pr) can be derived from that of 1 by simply removing one of the capping atoms lying on the C 3 axis, with only minor additional changes in the overall connectivity and shape of the molecule. This is reminiscent of the structural and chemical relationships between [M 8 (H){E 2 P(OR) 2 } 6 ] + and [M 7 (H){E 2 P(OR) 2 } 6 ] (M=Cu, Ag; E=S, Se) . The structure of cluster 3 (R= n Pr) can be derived from that of 2 by simply shifting off the capping atom lying on the C 3 axis, generating a chiral structure of C 1 symmetry and revealing structural isomerism in the Ag 20 core.…”
Section: Figurementioning
confidence: 96%
“…Central to this work is the hydride ligand, H – , the smallest closed‐shell anion known. Dhayal et al reported a [Cu 32 (H) 20 {S 2 P(O i Pr) 2 } 12 ] nanocluster containing the highest number of hydrides in a molecular cluster . The positions of 20 hydrides of the Cu 32 H 20 core were well resolved from high resolution data collected on TOPAZ for a 0.45 mm 3 single‐crystal sample with more than 51 atom‐% hydrogen (Figure ).…”
Section: Single‐crystal Diffractometersmentioning
confidence: 97%
“…All these observations suggest that the shape of a carrier plays an important role in determining the performance in drug delivery. At the moment, reports on the manipulation of the shape of Cu NCs as theranostic agents are scant, but such a possibility has been illuminated by a study which successfully converted polyhydrido Cu NCs into rhombus‐shaped Cu nanoparticles by making use of hydride addition to manipulate the growth of Cu NCs . This demonstrates the technical feasibility of designing and changing the shape of Cu NCs to meet practical needs.…”
Section: Design Of Cu Ncs For Theranostic Usementioning
confidence: 99%